2020
DOI: 10.1002/mds.28354
|View full text |Cite
|
Sign up to set email alerts
|

The Human Coronavirus Receptor ANPEP (CD13) Is Overexpressed in Parkinson's Disease

Abstract: The coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), 1 a new human coronavirus (hCoV) strain. The neuroinvasive potential of SARS-CoV-2 2 and recent research linking advanced age and neurological disease to COVID-19 severity 3 raise concerns for patients with Parkinson's disease (PD), who appear to be particularly susceptible to worse outcomes from COVID-19. 4 Using a combination of publicly available and in-house RNA sequencing (RNAseq) data, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…Interestingly, ACE2 and TMPRSS2, the two widely accepted receptors in SARS-CoV-2 cell entry, have been reported to be relatively low in endothelial cells of the human brain in two studies ( 52 , 72 ), which is consistent with the results shown in Figure 1 . Nevertheless, the coronavirus receptors ANEPE, AXL, and ENPEP were detected in the olfactory region and endothelial cells of human brain ( Figures 1B and 2C ), indicating that SARS-CoV-2 cell entry in human brain might require these three receptors rather than rely on ACE2 and TMPRSS2.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, ACE2 and TMPRSS2, the two widely accepted receptors in SARS-CoV-2 cell entry, have been reported to be relatively low in endothelial cells of the human brain in two studies ( 52 , 72 ), which is consistent with the results shown in Figure 1 . Nevertheless, the coronavirus receptors ANEPE, AXL, and ENPEP were detected in the olfactory region and endothelial cells of human brain ( Figures 1B and 2C ), indicating that SARS-CoV-2 cell entry in human brain might require these three receptors rather than rely on ACE2 and TMPRSS2.…”
Section: Discussionsupporting
confidence: 87%
“…43 Recently, ANPEP was described as a human coronavirus entry factor, 50 showing an important role in Parkinson's disease progression. 51 In our study, two of the ND FTND -specific DMS mapped to ANPEP correlated with methylation in brain tissue (cg06344992 and cg02008229). The last ND FTND -specific gene was SLC29A1, which mediates the uptake of nucleosides and has not been correlated to smoking in previous EWAS.…”
Section: Co-methylated Modules Associated With Ss and Nd Ftndsupporting
confidence: 50%
“…Another DMS mapped to the ANPEP is known as a diabetes risk gene, 49 recently identified as smoking‐associated in an EWAS examining the effects of cadmium and smoking in the Strong Heart Study cohort in blood tissue 43 . Recently, ANPEP was described as a human coronavirus entry factor, 50 showing an important role in Parkinson's disease progression 51 . In our study, two of the ND FTND ‐specific DMS mapped to ANPEP correlated with methylation in brain tissue (cg06344992 and cg02008229).…”
Section: Discussionmentioning
confidence: 99%
“…The patients with Parkinson's disease (PD) appear to be susceptible to worse outcomes from COVID-19. It is speculated that overexpression of ANP in these patients could be one of the causes for it [176,177].…”
Section: Aminopeptidase N (Apn Anpep Cd13): Receptor For Hcov-229ementioning
confidence: 99%